2015
DOI: 10.1063/1.4928595
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ag9(SiO4)2NO3 through a reactive flux method and its visible-light photocatalytic performances

Abstract: Ag9(SiO4)2NO3 was prepared by a reactive flux method. The structures, morphologies, and light absorption properties were investigated. Owing to the polar crystal structure, an internal electric field can be formed inside the material, which can facilitate the photogenerated charge separation during the photocatalytic process. Based on both the wide light absorption spectra and high charge separation efficiency originated from the polarized internal electric field, Ag9(SiO4)2NO3 exhibit higher efficiency over A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The longert he lifetime is, the more possiblet hat photogenerated electrons and holes participate in photocatalytic re-actions. [40,41] As shown in Figure 8, the excited state of CdS LDH displays am uch longerl ifetimet han that of CdS CdðOHÞ 2 .T he average lifetimew as determined using at wo-exponential decay function: t av ¼ t 1 a 1 þ t 2 a 2 (t 1 , t 2 are the lifetime, a 1 , a 2 are normalized pre-exponential factors). The average lifetime of CdS LDH is t = 114.40 ns, much longer than that of CdS CdðOHÞ 2 (t = 62.37 ns).…”
Section: Pl and Time-resolved Pl Spectramentioning
confidence: 99%
“…The longert he lifetime is, the more possiblet hat photogenerated electrons and holes participate in photocatalytic re-actions. [40,41] As shown in Figure 8, the excited state of CdS LDH displays am uch longerl ifetimet han that of CdS CdðOHÞ 2 .T he average lifetimew as determined using at wo-exponential decay function: t av ¼ t 1 a 1 þ t 2 a 2 (t 1 , t 2 are the lifetime, a 1 , a 2 are normalized pre-exponential factors). The average lifetime of CdS LDH is t = 114.40 ns, much longer than that of CdS CdðOHÞ 2 (t = 62.37 ns).…”
Section: Pl and Time-resolved Pl Spectramentioning
confidence: 99%
“…Calculations method about the CB and VB was according to our previous work. [24,25] And the estimated CB and In order to evaluate photocatalytic activities of as-prepared samples. Photodegradation of organic dye solutions and photocatalytic O2 production experiments were carried out.…”
Section: Photocatalytic Experimentsmentioning
confidence: 99%
“…[60] Based on above research, an internal polar electric fieldw as found in the crystal structure of Ag 9 (SiO 4 ) 2 NO 3 ,i nw hich the separated single SiO 4 tetrahedra and NO 3 polyhedra are coordinated with Ag cations. [61] Due to d 10 -d 10 interactions of the short AgÀAg bonds, Ag 9 (SiO 4 ) 2 NO 3 exhibited stronga bsorption in the visible-light region. Calculationsc onfirmed that the CB and VB of Ag 9 (SiO 4 ) 2 NO 3 are mainly composed of Oa nd Ag atoms, respectively.U pon light irradiation of Ag 9 (SiO 4 ) 2 NO 3 , electrons weree xcited andt ransfer from the VB to the CB, which can be described as electron transfer from Oatoms to coordinated Ag atoms in the material.…”
Section: Silver Silicate Polar Photocatalystsmentioning
confidence: 99%
“…Calculationsc onfirmed that the CB and VB of Ag 9 (SiO 4 ) 2 NO 3 are mainly composed of Oa nd Ag atoms, respectively.U pon light irradiation of Ag 9 (SiO 4 ) 2 NO 3 , electrons weree xcited andt ransfer from the VB to the CB, which can be described as electron transfer from Oatoms to coordinated Ag atoms in the material. [61] The existence of NO 3 À groups in the crystal structure of Ag 9 (SiO 4 ) 2 NO 3 can generate internal electric fields, and its directioni sin accord with the directions of electron and hole migration (Figure 8a). Therefore, an additional driving force facilitates the charge separation and result in enhanced photocatalytic activities of Ag 9 (SiO 4 ) 2 NO 3 in oxygen evolution (Figure 8c).…”
Section: Silver Silicate Polar Photocatalystsmentioning
confidence: 99%
See 1 more Smart Citation